Tabarru’ Fund and Solvability In Affecting The Profitability of The Life Insurance Sharia in Indonesia - Happy Sista Devy (ITB AAS INDONESIA Surakarta, 2022)
The purpose this research is to determine influence between solvability and tabarru’ fund on profitability in the life Insurance of Sharia in Indonesia. This research using data analysis test detailed statistics with multiple linier regression by statistical program E-view. Research found that investment by companies it can affect the financial performance or profitability. The ability of the sharia insurance company in Indonesia adequate to repay short-term not influenced on the ability of the company to pay the debt through the ratio of DER. So it is possible that the results obtained the ratio of DER cannot affect ROA. Tabarru’ fund can influence to profit generated by the company.